Aparigraha- The Age Old Philosopy Of Indian Scriptures- The New Face of Global Consumerism in The Post Covid-19 Era - Dhingra, Manish; Dhingra, Vaishali (The journal of contemporary issues in business and government, 2021)
The aim of this paper is to capture the essence of the timeless wisdom imparted by Indian scriptures and philosophy and use its wisdom for answering the novel consumerism in the wake of COVID-19 and provide a sustainable solution to the materialism ridden society. This paper addresses the issue of the new face of consumerism during the onset of COVID-19 in the perspective of ‘Aparigraha’ as taught by the ancient scripture Bhagwad Gita. Across the world people and governments are grappling with the issue of nouveau consumerism which is laden with hoarding, exploitation of resources, greed and materialism. Since the outbreak of the pandemic COVID-19, there has been a slowdown in economy, downturn in the morale of people and stress is looming large among the masses. A new face of consumerism has already started emerging wherein people have become more conscious about their food habits, health, exercise and spending on consumables. In the COVID-19 era when the global economy has slowed down, the age-old philosophy as mentioned in verse 10 of Chapter 6 of Srimad Bhadwad Gita provides a ready solution.